DISCONTINUITY OF FAMILY PLANNING METHODS AND ASSOCIATED FACTORS AMONG WOMEN OF REPRODUCTIVE AGE (15–49 YEARS) IN NGOMA DISTRICT, RWANDA - Hategekimana Jean Baptiste & Dr. Kevin Nwanna (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
Background: Discontinuity of family planning methods shortly after initiation poses a significant public health challenge in low and middle-income countries. According to the 2019–2020 Rwanda Demographic and Health Survey, 30% of family planning users in Rwanda discontinued their method within 12 months of starting. Ngoma District reported the highest discontinuation rate at 31%. This study aimed to investigate the factors contributing to the discontinuation of family planning methods among women of reproductive age in Ngoma District, Rwanda. Materials and Methods: A cross-sectional study was conducted at seven key health centers in Ngoma District, chosen for their high utilization by women using family planning methods. A total of 323 women participated voluntarily, completing a pre-tested self-administered questionnaire through systematic sampling. Collected data were carefully checked, coded, and analyzed using SPSS version 25. Descriptive statistics, such as frequency, mean, standard deviation, and percentage, were computed. Bivariate and multiple logistic regression analyses were performed to explore factors influencing discontinuity of family planning methods. Variables with p-values less than 0.05 in the bivariate analysis were included in the multiple logistic regression to control for potential confounding factors, with statistical significance set at p < 0.05. Results: The study revealed that a majority of respondents were aged 26-35 years (50.5%), married (89.8%), and had health insurance coverage (98.5%). Most had primary education (82.7%) with a smaller proportion having secondary education (9.0%). Additionally, nearly all were engaged in farming (98.5%) and identified as Christian (96.6%). The prevalence of discontinuity in family planning methods in Ngoma District was 31%, while 69% continued to use contraceptives. Respondents demonstrated a high overall knowledge score of 94.1% on family planning. Factors significantly linked to discontinuity included possession of health insurance, religious affiliation, experience of side effects, partner opposition, and desire for additional children. Discussion: The findings underscore the importance of addressing factors such as health insurance coverage, religious beliefs, side effects, partner dynamics, and reproductive desires in ensuring sustained use of family planning methods among women in Ngoma District. Strategies to improve counseling for new users, reminder systems for method resupply appointments, and support for dissatisfied users could potentially mitigate discontinuation rates. Engaging religious leaders and sensitizing husbands about the benefits of family planning may also enhance acceptance and support for contraceptive use among women. Conclusion: The study concludes that possession of health insurance, religious affiliation, partner opposition, and desire for more children significantly influence discontinuity of family planning methods among women of reproductive age in Ngoma District, Rwanda. Counseling strategies addressing side effects and switching options, along with involvement of religious and community leaders, are recommended to improve continuity and sustainability of family planning services.